Probing Charge Carrier Properties and Ion Migration Dynamics of Indoor Halide Perovskite PV Devices Using Top- and Bottom-Illumination SPM Studies - Alosaimi, Ghaida; Shin, So Jeong; Chin, Robert Lee; Kim, Jong H.; Yun, Jae Sung; Seidel, Jan (Advanced Energy Materials, 2021)
Recently, perovskite solar cells have shown excellent performance under indoor light conditions. In a new approach using directional illumination combined with nanoscale scanning probe microscopy (SPM) characterization, morphology dependent-charge transport measurements are performed to provide a comprehensive understanding of the optoelectronic behavior of (FAPbI3)0.85(MAPbBr3)0.15 containing 5 vol% cesium (Cs5vol%) with various electron transport layers (ETLs), i.e., SnO2, c-TiO2, and [6,6]-phenyl-C61-butyric acid methyl ester/SnO2 under indoor light. This approach allows the identification of the charge transport properties of the perovskite film and the perovskite/ETL interface separately. The light is applied from the top of the perovskite film to study the electronic properties of the surface. Lower photocurrent and lower surface photovoltage (SPV) are observed under top-illumination conditions. The electronic interface behavior is investigated using bottom-illumination and short excitation wavelengths, such as blue LED light. Higher photocurrent and higher SPV are observed under blue light illumination from the bottom. These results suggest that the charge transport capability is enhanced near the p–n junction. Conductive atomic force microscopy results show that SnO2 enhances the charge collection properties of the perovskite's grain boundaries (GBs). Kelvin probe force microscopy results confirm that SnO2 exhibits homogeneous and high surface potential because of the lowest trap states at GBs.
Keywords: Charge carrier properties; Charge collection properties; Conductive atomic force microscopy; Electron transport layers; Illumination conditions; Kelvin probe force microscopy; Transport capabilities; [6 ,6]-phenyl-C61-butyric acid methyl esters; grain boundaries; indoor photovoltaic cells; surface potential; triple-cation perovskites